Positive Politeness Strategies in Podcast Interactions with Individuals Experiencing Dissociative Identity Disorder: A Pragmatic Study - Bryan Raferty Antonio; Irman Nurhapitudin; Cipto Wardoyo (Journal of English Language and Education, 2026)
Positive politeness is a pragmatic strategy used to protect the hearer’s positive face while fostering solidarity, mutual respect, and interpersonal rapport during interaction. Grounded in Brown and Levinson’s (1978) politeness theory, this study investigates the types and functions of positive politeness strategies employed in the YouTube podcast episode I Have Dissociative Identity Disorder published by the MedCircle channel. The episode was selected because it discusses the sensitive topic of Dissociative Identity Disorder (DID), a complex mental health condition that requires careful and empathetic communication. This study employed a qualitative discourse analysis approach. The data consisted of utterances produced by the host, the guest speaker, and the guest speaker’s alternate identities. The analysis identified 134 instances of positive politeness strategies. The most frequently used strategy was presupposing, asserting, or raising common ground (75 occurrences), whereas asserting or presupposing the speaker’s knowledge of the hearer’s wants and giving or asking for reasons each occurred only once. Four strategies—using in-group identity markers, offering, promising, being optimistic, and assuming reciprocity—were absent. Overall, the findings demonstrate that speakers predominantly relied on establishing common ground, expressing interest, and seeking agreement to facilitate supportive and empathetic communication when discussing sensitive mental health issues.